Growing in to autism - Thom-Jones, Sandra (Melbourne University Publishing, 2022)
From the outside looking in, Sandra Thom-Jones was living a successful life: she had a great career, a beautiful home, a caring husband, two loving sons and supportive friends. But from the inside looking out, she was struggling to make sense of her place in the world, constantly feeling overwhelmed and exhausted, and convinced that her challenges with daily life just meant that she had to try harder. In Growing In to Autism, Thom-Jones tells the story of gradually realizing that she was autistic, and that she experienced the world in ways which were markedly different from neurotypical people. This was a profound awakening - throughout her life she had been masking her true self and this effort had come at great physical, mental and emotional cost. Applying her skills as an experienced and expert researcher, Thom-Jones delved into the literature on autism in adults, learning much more than she already knew as a parent of two autistic boys. Part personal, funny, endearing and enlightening memoir, and part rigorous explication of the nature of autism, Growing in to Autism is a book for all people, memorably conveying the need for better understanding and ways of making space for a group of individuals in our society who have so much to offer.